-13=7p-12-6p

Simple and best practice solution for -13=7p-12-6p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13=7p-12-6p equation:


Simplifying
-13 = 7p + -12 + -6p

Reorder the terms:
-13 = -12 + 7p + -6p

Combine like terms: 7p + -6p = 1p
-13 = -12 + 1p

Solving
-13 = -12 + 1p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-1p' to each side of the equation.
-13 + -1p = -12 + 1p + -1p

Combine like terms: 1p + -1p = 0
-13 + -1p = -12 + 0
-13 + -1p = -12

Add '13' to each side of the equation.
-13 + 13 + -1p = -12 + 13

Combine like terms: -13 + 13 = 0
0 + -1p = -12 + 13
-1p = -12 + 13

Combine like terms: -12 + 13 = 1
-1p = 1

Divide each side by '-1'.
p = -1

Simplifying
p = -1

See similar equations:

| 36r^9-9r^6+54r^3= | | 7(3x-4)=17x | | x+6/5+x-1/4=2 | | 11=8p-14-7p | | n^2=4n+5 | | 1/2y-1/3x-1=0 | | -3=3p+11-2p | | 6=-6p-10+7p | | a+3ab-4ab= | | 3x-5+9x=-15 | | 8x^3-49x^2+6x=0 | | -8+10=9x+17 | | 1+a+x^2=p | | -9=-6p-7+7p | | y-4=(x-7)(x-7) | | 3=-4.5+4y | | -9=5p-12-4p | | x+19=139 | | 22x=-12 | | 2=-4.5+4y | | -16=-5(8n+3) | | -6=-9p+14+10p | | 1=-4.5+4y | | 121b^2-100= | | 0=-4.5+4y | | 2x-19=1421 | | 27=6+8+c | | 10x+20/25x+20 | | 191=-3x+7(4x-12) | | -6=-5p-12+6p | | 2z-6-7=-30 | | -28n^2=-96-184n |

Equations solver categories